Análise da confiabilidade de estruturas sujeitas a controle passivo e ativo de vibrações - Cunha, Leandro Rodrigues (2013)
This dissertation is devoted to the reliability analysis of structures subjected to active and passive vibration control, with emphasis on the use of First Order Reliability Method (FORM) and Second Order Reliability Method (SORM). These methods are used to evaluate the reliability indices and the associated failure probability, considering that the random variables are modeled by probability density functions. Three techniques of vibration control are considered, namely: active control using PZT stack actuators, passive control based on dynamic vibration absorbers, and passive control based on piezoelectric transducers connected to resonant shunt circuits. For each technique, limit state functions are defined related to the operational limitations or design requirements. Their evaluation is made from structural responses obtained from finite element models. For each control technique, numerical applications of FORM and SORM are carried-out for a two-dimensional truss, defined as the structure of interest. To assess the accuracy of the reliability estimations provided by those methods, Monte Carlo Simulations are also performed. The numerical results enable to put in evidence specific characteristics of each control technique as related to reliability. Specifically, for two of them it is verified the occurrence of atypical geometrical forms of the safety and failure domains, which preclude the use of FORM and SORM. In general, the results confirm the importance and convenience of performing reliability assessment of structures subjected to vibration control procedures.